Children’s Positive Attitude towards Activity is the Foundation of Humanity Education - Bakutytė, Rima (Acta Paedagogica Vilnensia, 1999)
This article disclose connection between II-IV form children's humanity and their attitude towards activity. The research data show us rather close interaction between children's attitude towards activity and their humanistic behaviour which is observed in relationship with classmates, teachers and parents. Furthermore, research data disclose some connection between positive attitude towards activity and perception of humanistic values, favourable attitude towards them.
Keywords: humanity; humanity education; humanistic behaviour; humanistic values; activity